Green Synthesis of Cobalt–Zinc Ferrites and Their Activity in Dye Elimination via Adsorption and Catalytic Wet Peroxide Oxidation - Mariia Liaskovska; Tetiana Tatarchuk; Volodymyr Kotsyubynsky (Metals)
Zinc-substituted cobalt ferrites were obtained by a green method using a black grape extract as a reductant and fuel. XRD analysis confirmed the spinel structure of the synthesized ferrites. An increase in the lattice constant is explained by increased Zn content. SEM analysis confirmed changes in surface morphology, whereas FTIR spectra demonstrated the presence of organic species in the samples, which originated from grape extract. The content of Co(II) ions in octahedral sites as a function of the ratio between Fe(III) ions in A- and B-sites was calculated from Mössbauer data. pHPZC rose from 7.85 to 8.13 with an increase in zinc content, indicating a positive charge of the adsorbent surface at natural pH. The adsorption–catalytic properties of the spinel samples were investigated in terms of Congo Red (CR) dye removal. The mechanism of CR adsorption on the ferrite surface includes electrostatic and donor–acceptor interactions with the adsorbent surface. Furthermore, the sample with x(Zn) = 0.4 exhibited the highest degradation rate constant k = 0.102 min−1 in the peroxide oxidation of CR, whereas the sample with x(Zn) = 1.0 exhibited the highest adsorption capacity. The electron transfer between ferrite samples and hydrogen peroxide was evidenced using electrochemical tests. The green-synthesized Co-Zn ferrites demonstrate a big potential as adsorbents/catalysts for water treatment.